A model of community development and gender equity through access to information technology - Majola, Pretty Lilly (Department of Communication Science, University of the Free State, 2006)
Marginalised people, in their everyday life, do not know where and how to access information for their own survival and development. This information would, if correctly applied, enable them to participate in social, political and economic processes associated with development. The three key aspects that articulate a model of community development through information are gender, participation, and Information Communication Technologies (ICTs). From the literature review, practical experience and case studies, it has been clear that most community projects do not explicitly address the gender, participation and ICT aspects. The model of community development presented in this article is a tool for making local and external information available and accessible to marginalised members of a community so that they can use it for their own development.
Keywords: Information Communication Technologies (ICTs); Information access; Marginalised people; Gender equity; Community development